N-Acyliminium Ion Chemistry: Improving the Access to Unsaturated γ-Lactams and Their N-α-Methoxylated Derivatives: Application to an Expeditive Synthesis of (±)-Crispine A - Souquet, Florence; Drici, Wassila; Fayssal, Sandra Abi; Lazouni, Imane; Thueillon, Sébastien; Pérard-Viret, Joëlle (Synthesis, 2020)
An improved synthesis of unsaturated γ-lactams by condensation of various primary amines with 2,5-dimethoxy-2,5-dihydrofuran is described. A modified mechanism for this reaction is suggested. Synthesis of their N-α-methoxylated derivatives, as N-acyliminium ion precursors, is also reported. Finally, a short synthesis of (±)-crispine A is presented as an illustrative application.
Keywords: unsaturated γ-lactams; aza-heterocycles; N-acyliminium; 5-methoxypyrrolidin-2-one; crispine A